Urban thoracic trauma: diagnosis and initial treatment of non-cardiac injuries in adults - Vasileios Leivaditis; Athanasios Papatriantafyllou; Ioanna Akrida; Michail Galanis; Emmanouil Dimopoulos; Anastasia Papaporfyriou; Benjamin Ehle; Efstratios Koletsis; Nikolaos Charokopos; George Pappas-Gogos; Francesk Mulita; Georgios-Ioannis Verras; et al. (Medicinski glasnik, 2024)
This comprehensive review aims to delineate the prevailing non-cardiac thoracic injuries occurring in urban environments following initial on-site treatment and subsequent admission to hospital emergency departments. Our study involved a rigorous search within the PubMed database, employing key phrases and their combinations, including "thoracic injury," "thoracic trauma," "haemothorax," "lung contusion," "traumatic pneumothorax," "rib fractures," and "flail chest." We focused on original research articles and reviews. Non-cardiac thoracic injuries exhibit a high prevalence, often affecting poly-trauma patients, and contributing to up to 35% of polytrauma-related fatalities. Furthermore, severe thoracic injuries can result in a substantial 5% mortality rate. This review provides insights into clinical entities such as lung contusion, traumatic haemothorax, pneumothorax, rib fractures, and sternal fractures. Thoracic injuries represent a frequent and significant clinical concern for emergency department physicians and thoracic surgeons, warranting thorough understanding and timely intervention.
Keywords: hematothorax; pneumthorax; tho-racic trauma; urban trauma